The recognition of anions using delayed lanthanide luminescence: the use of Tb(iii) based urea functionalised cyclen complexes - GUNNLAUGSSON, THORFINNUR (Royal Society of Chemistry, 2009)
A cyclen based lanthanide luminescent sensor, Tb.1, has been developed by taking advantage of a combination of hydrogen bonding and f-metal ion coordination binding sites for anionic species. Analysis of the ground state, the emission from the singlet and the Tb(III) excited states clearly show the ability of the Tb(III) complex to signal the presence of anions in CH3CN, through multiple binding interactions consisting of hydrogen bonding and metal coordination. The delayed lanthanide luminescence from the Tb(III) diaryl?urea complex was found to be significantly enhanced only upon recognition of H2PO4-, at the same time as displaying good selectivity over other competitive anions, such as CH3COO-.
PUBLISHED
Keywords: Chemistry